Prodromal Spinocerebellar Ataxia Type 2 Subjects Have Quantifiable Gait and Postural Sway Deficits. Issue 2 (27th October 2020) - Velázquez‐Pérez, Luis; Rodriguez‐Labrada, Roberto; González‐Garcés, Yasmani; Arrufat‐Pie, Eduardo; Torres‐Vega, Reidenis; Medrano‐Montero, Jacqueline; Ramirez‐Bautista, Beatriz; Vazquez‐Mojena, Yaimeé; Auburger, Georg; Horak, Fay; Ziemann, Ulf; Gomez, Christopher M.
Abstract: Background: The search for valid preclinical biomarkers of cerebellar dysfunction is a key research goal for the upcoming era of early interventional approaches in spinocerebellar ataxias. This study aims to describe novel preclinical biomarkers of subtle gait and postural sway abnormalities in prodromal spinocerebellar ataxia type 2 (pre‐SCA2). Methods: Thirty pre‐SCA2 patients and their matched healthy controls underwent quantitative assessments of gait and postural sway using a wearable sensor‐based system and semiquantitative evaluation of cerebellar features by SARA (Scale for the Assessment and Rating of Ataxia) score. Results: Quantitative analysis of natural gait showed a significantly larger variability of the swing period, toe‐off angle and toe‐out angle in pre‐SCA2, and larger mean coronal and transverse ranges of motion of the trunk at the lumbar location and of the sagittal range of motion of the trunk at the sternum location compared to controls. During tandem gait, pre‐SCA2 subjects showed larger lumbar, trunk, and arm ranges of motion than controls. Postural sway analysis showed excessive body oscillation that was increased in tandem stance. Overall, these abnormalities were detected in pre‐SCA2 patients without clinical evidence of abnormalities in SARA. The toe‐off angle and swing time variability were significantly correlated with the time to ataxia onset, whereas the toe‐off angle and transverse range of motion at trunk position during tandem gait were significantly associated with the SARA score. Conclusions: This study demonstrates early alteration of gait and postural sway control in prodromal SCA2 using a wearable sensor‐based system. This offers new pathophysiological hints into this early disease stage and provides novel potential biomarkers for future clinical trials. © 2020 International Parkinson and Movement Disorder Society